Lessons from the field for working in Healthy Stadia: physical activity practitioners reflect on 'sport'. Issue 2 (1st February 2017) - McKenna, Jim; Quarmby, Thomas; Kime, Nicky; Parnell, Daniel; Zwolinsky, Stephen
Abstract: Drawing on four areas of our ongoing work, each with its own distinctive relevance to the Healthy Stadia agenda, this paper addresses the tension inherent to programmes aiming to promote physical activity through sport. Our experiences highlight often unresolved, but certainly resolvable, tensions between the aspirations of the respective agendas. These are not small matters; better Public Health is a powerful driver of the Healthy Stadia agenda. In particular, we notice that the desire for sporting, over health, improvement can be an important challenge point. In the hard-to-reach groups we work with, sport often has strong – and only occasionally positive – connotations. Equally, the importance of generating powerful social experiences is seen in the PA 'camp' as being an imperative for encouraging the involvement of hard-to-reach groups. In contrast, in sport-oriented programmes, this is more likely to be seen as a happy bi-product of a good sport experience .